Development of a Coding for Kids Thunkable Module: A Learning Guide to Create Games Using Code Blocks at Algoland Academy - Amelia Uswatun Khasanah; Dyah Darma Andayani; Satria Gunawan Zain (PT. Global Research Collaboration, 2026)
Background/Context: The accelerating pace of digital transformation has intensified the demand for digital literacy, with coding increasingly recognized as a foundational competency essential for success in the 21st century. Algoland Academy faces a critical instructional challenge stemming from the absence of a structured, curriculum-aligned learning module based on the Thunkable platform, despite a demonstrable and growing interest in this platform among its network of partner schools in Makassar City. Objective/Purpose: This study aimed to develop a Thunkable-based Coding for Kids module designed as an instructional guide for creating educational games using code blocks, and to evaluate the module's validity, practicality, and learner responses. Method: This study employed the Four-D (4D) instructional development model, encompassing the Define, Design, Develop, and Disseminate stages. Data were collected through interviews, literature reviews, documentation, and questionnaires, and subsequently analyzed using a descriptive quantitative approach. Results: The module achieved a “Very Valid” classification, with a content validity score of 97.20% and a media validity score of 96.94%. Practicality assessments yielded progressive results across three trial stages: 79.17% in the individual trial “Practical”, 87.73% in the small group trial “Very Practical”, and 85.24% in the large group trial “Very Practical”. The learner response assessment, administered to 30 student participants, produced an overall mean score of 88.16%, classified as “Positive”, with the motivation and benefits dimension achieving the highest score at 88.93%, reflecting strong learner engagement and enthusiasm throughout the instructional process Conclusion: The Thunkable-based Coding for Kids module was determined to be valid, practical, and suitable for implementation as a digital literacy-based coding instructional resource for elementary-aged learners. The module's game-based learning approach, child-friendly design, and structured content organization collectively support independent learning, learner engagement, and coding competency development. These findings carry meaningful practical significance, as the module holds strong potential to serve as a replicable instructional reference for non-formal educational institutions and formal elementary schools alike, particularly in light of Indonesia's recent policy mandating coding as an elective subject beginning in the 2025/2026 academic year.